Customer satisfaction on service quality of Grand Bluewave Hotel Shah Alam / Fazliah Noor Mohd Fouzi - Mohd Fouzi, Fazliah Noor (2015)
The study was conduct to examine the customer satisfaction on service quality of Grand BlueWave Hotel Shah Alam. Data were gathered using questionnaires from a population of Grand BlueWave Hotel Shah Alam. The result demonstrated that service quality had significant and positive associations between the customer’s satisfaction and Grand BlueWave Hotel Shah Alam. The objectives that can be seen would be to identify level of customer’s satisfaction on Grand BlueWave Hotel Shah Alam, to identify which service quality has the most attribution on Grand BlueWave Hotel Shah Alam and to provide recommendations to Grand BlueWave Hotel Shah Alam to improve its service quality. Respondents in this study were the guests and employees based in the Grand BlueWave Hotel Shah Alam. Descriptive research has been adopted for this study. The findings showed that the most of the customers are satisfied with the service provided and service quality dimension seems to have influence with customer satisfaction. Recommendations are put on how to improve and increase customer’s satisfaction on the service provided by Grand BlueWave Hotel Shah Alam.